Introduction to Freva – A Free Evaluation System Framework for Earth System Modeling. (2nd June 2021) - Kadow, Christopher; Illing, Sebastian; Lucio-Eceiza, Etor E.; Bergemann, Martin; Ramadoss, Mahesh; Sommer, Philipp S.; Kunst, Oliver; Schartner, Thomas; Pankatz, Klaus; Grieger, Jens; Schuster, Mareike; Richling, Andy; et al.
Freva – Free Evaluation System Framework for Earth system modeling is an efficient solution to handle evaluation systems of research projects, institutes or universities in the climate community. It is a scientific software framework for high performance computing that provides all its available features both in a shell and web environment. The main system design is equipped with the programming interface, history of evaluations, and a standardized model database. Plugin – a generic application programming interface allows scientific developers to connect their analysis tools with the evaluation system independently of the programming language. History – the configuration sub-system stores every analysis performed with the evaluation system in a database. Databrowser – an implemented meta data system with its advanced but easy-to-handle search tool supports scientists and their plugins to retrieve the required information of the database. The combination of these three core components, increases the scientific outcome and enables transparency and reproducibility for research groups using Freva as their framework for evaluation of Earth system models.